The Analysis of Proenvironmental Behavior (PEB) through by Personality at Senior High School Students - Desi Eka Nur Fitriana; Mieke Miyarsah; Rusdi Rusdi (Indonesian Journal of Science and Education (IJOSE), 2019)
Pro-environment behavior (PEB) is a behavior that seeks to minimize the negative impact on the environment which is influenced by several factors such as personality. This study aimed to analyze the direct effect of personality on pro-environment behavior. This research was conducted under quantitative approach with a causal survey method and analyzed used path analyze. The respondents consisted of 200 students of class XI MIA SMAN 1 Tangerang Regency. This research shown that there was positive direct effect of personality on pro-environment behavior with a path analysis coefficient  0.159.Keywords: Personality, Pro Environment Behavior, path analyze